Examen especial al componente inventarios de la empresa Estudios S.A del 1 al 30 de junio del 2018. - Huanca Ortiz, Juana Tatiana (My University, 2019)
The financial audit is a process that allows the evaluation of the accounts and records made in an entity, to confirm the veracity of the information presented in the financial statements. Therefore, the audit process is considered as a fundamental tool, because it provides the necessary guidelines for the participants of a company to adequately develop their activities. Within this process, a special examination can be carried out to evaluate a specific account, through which it is verified whether the transactions and economic events are properly recorded. To do this, the case study to be developed is then planned, in which a special examination is requested to the inventories account of the company ESTUDIOS S.A., for the period from June 1 to June 30, 2018; for this, it is requested to evaluate the internal control of the entity; establish the level of risk and confidence; determine the sample size; prepare the analytical certificates; make adjustments and reclassifications; and present the audited Financial Statements. The present investigation will focus on a qualitative and quantitative analysis, applying the descriptive methodology; and the method to be used is the non-experimental case study. Within the investigation, it could be found that the personnel does not comply with the internal control of the company, for this reason the level of risk is high and the level of trust is low.
La auditoría financiera es un proceso que permite evaluar las cuentas y registros realizados en una entidad, para confirmar la veracidad de la información presentada en los estados financieros. Por ende, el proceso de auditoría es considerado como una herramienta primordial, debido a que brinda las pautas necesarias para que los participantes de una empresa desarrollen adecuadamente sus actividades. Dentro de este proceso se puede realizar un examen especial, para evaluar a una cuenta determinada, que permite verificar si las transacciones y hechos económicos están adecuadamente registrados. Para ello, se planeta a continuación el caso práctico a desarrollar, en el cual se pide realizar un examen especial a la cuenta inventarios de la empresa ESTUDIOS S.A., por el periodo comprendido del 1 al 30 de junio del 2018; para esto se solicita evaluar el control interno de la entidad; establecer el nivel de riesgo y confianza; determinar el tamaño de la muestra; elaborar las cédulas analíticas; realizar los ajustes y reclasificaciones; y presentar el Estado de Situación Financiera auditado. La presente investigación se centrará en un análisis cualitativo y cuantitativo, aplicando la metodología descriptiva; y el método a ser utilizado es el estudio de caso no experimental. Dentro de la investigación se pudo encontrar que el personal no cumple con el control interno de la empresa, por tal razón el nivel de riesgo es alto y el nivel de confianza es bajo.
Keywords: AUDITORÍA; EXAMEN ESPECIAL; AUDITORÍA FINANCIERA; CONTROL INTERNO; INVENTARIOS